Komunikasi Reseptif dalam Meningkatkan Prestasi Belajar Anak - Adiwiria, Pien Supinah (FIkom Unisba, 2007)
Education is the process of transforming knowledge into the process of learning and teaching in the school system. Dwyer and Barker stated that the most dominant learning and teaching process is receptive communication as applied in the act of listening and reading. Logically, the senses being actively engaged in such process are hearing and visioning facilities. An observation toward school practices proved that listening and reading activities become the main part of academic skills to be acquired by students. It is concluded that receptive communication allows students to absorb knowledge and technology effectively which in turn will increase students’ learning achievement.